2016
DOI: 10.3171/2016.2.peds15702
|View full text |Cite
|
Sign up to set email alerts
|

A decision-making guide for the closure of myelomeningocele skin defects with or without primary repair

Abstract: OBJECTIVE The closure of the skin defect in myelomeningocele (MMC) repair is an essential step that determines the quality of the surgical result. The success of surgical results is related to the decision to use the most suitable techniques, namely flaps or primary closure. The aim of this study was to evaluate the effectiveness of a decision-making guide to determine whether to use primary repair or a flap for the closure of skin defects that occur in MMC. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Previous literature has suggested that the diameter of the lesion should dictate its method of closure; traditionally flap reconstruction is recommended for defects that are > 5 cm in diameter [ 7 , 8 ]. Increasingly, a more tailored approach incorporating the location, shape and area, in addition to lesion length, has been reported [ 5 , 9 , 10 ]. Decisions on closure made on an individual basis instead of the width of the defect yield lower complication rates [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous literature has suggested that the diameter of the lesion should dictate its method of closure; traditionally flap reconstruction is recommended for defects that are > 5 cm in diameter [ 7 , 8 ]. Increasingly, a more tailored approach incorporating the location, shape and area, in addition to lesion length, has been reported [ 5 , 9 , 10 ]. Decisions on closure made on an individual basis instead of the width of the defect yield lower complication rates [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increasingly, a more tailored approach incorporating the location, shape and area, in addition to lesion length, has been reported [ 5 , 9 , 10 ]. Decisions on closure made on an individual basis instead of the width of the defect yield lower complication rates [ 5 ]. The condition of the skin surrounding the lesion is also an important variable to consider when deciding upon the method of closure.…”
Section: Discussionmentioning
confidence: 99%
“…Every fourth patient who undergoes surgery for NTD will have a large wound, difficult to be closed primarily. [5] Effective closure provides tension-free repair, ensuring adequate soft tissue cover of the repaired site; thereby preventing cerebrospinal fluid leakage and promoting wound healing, especially in larger defects. Different local flaps and grafts have been described with variable results in literature.…”
Section: Discussionmentioning
confidence: 99%
“…Also, although all lipo-MMC could be closed primarily, all six patients with kyphosis and six patients with rachischisis needed rhomboid flaps for wound closure. In a recent study, Kemaloğlu et al [5] emphasized the importance of ratio of the dimensions of the wound in decision-making for wound closure. Campobasso et al [8] found Limberg’s flap to provide stable wound closure with minimal complications in their series of large MMC.…”
Section: Discussionmentioning
confidence: 99%
“…Wound necrosis with dehiscence following repair of MMC is a serious impediment to recovery that can result in CSF leakage, damage of exposed neural tissues and life-threatening infection. 7 The key etiologic factors in the pathophysiology of these wounds are hematoma formation, surgical-site infection and local tissue ischemia often associated with high wound tension. 8 Wound complications occur postoperatively in 24% of MMC patients, half of which are superficial wound dehiscence, while major flap necrosis requiring surgical reconstruction complicates 1–8% of repairs.…”
Section: Discussionmentioning
confidence: 99%